Financial health overview of pharmaceutical sector companies listed on IDX using profitability ratios before, during, and after the COVID-19 pandemic - Amalina Nur Arifah; Andita Sulistyowati; Agniya Thahira (PT Aksara Indo Rajawali, 2026)
Purpose – This paper analyzes the financial health of selected pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) using profitability ratios across periods before (2019), during (2020–2021), and after (2022) the Covid-19 pandemic, highlighting sector resilience amid economic shocks. Design/methodology/approach – A descriptive quantitative approach uses secondary data from audited financial statements of four companies: PT Darya-Varia Laboratoria Tbk (DVLA), PT Pyridam Farma Tbk (PYFA), PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO), and PT Tempo Scan Pacific Tbk (TSPC). Profitability ratios include Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Operating Return on Assets (OROA), and Return on Equity (ROE), with peer-group comparisons and DuPont analysis. Findings – Profitability improved during the pandemic (2020–2021), driven by surging demand for health products. SIDO consistently outperformed peers. PYFA showed a strong recovery in 2022. GPM declined post-pandemic due to rising costs. Overall, the sector demonstrated counter-cyclical resilience. Research limitations – The study covers only four companies and focuses solely on profitability ratios, excluding liquidity, solvency, or macroeconomic modeling. Suggestions for future research include expanding the sample and incorporating additional metrics. Implications – Findings inform investors and policymakers on the pharmaceutical sector's resilience during crises and emphasize post-pandemic cost management strategies. Originality – This study fills a gap by extending profitability analysis into the post-pandemic period (2022) with peer benchmarking, providing a complete trajectory across pandemic phases.